Egg morphology of six East Palaearctic species of the genus Ephemera Linnaeus (Ephemeroptera: Ephemeridae) - Tiunova, Tatiana M. (Zootaxa, 2024)
The eggs of six East Palaearctic species in the subgenera Ephemera Linnaeus s.s. and Sinephemera Kluge from the Russian Far East are investigated by scanning electron microscopy. Eggs of the subgenus Ephemera have a thick adhesive layer ranging from 1.3 to 3.0 µm. In species of the subgenus Sinephemera, the adhesive layer is thin, amorphous, and 0.5 µm in E. (S.) shengmi Hsu, while in the other two species it is presented in the form of a thin film. All studied species have micropyles of the “tagenoform type,” with the exception of E. (S.) shengmi, in which the micropyle can be classified as linear. The shape of the sperm guide is species-specific and is clearly visible only on the adhesive layer. The structure of the chorion varies markedly among the species studied. So in E. (S.) japonica McLachlan, it is practically smooth; in E. (E.) transbajkalica Tshernova, it is reticulate; in E. (E.) orientalis McLachlan and E. (S.) strigata Eaton, it is finely wrinkled; and in E. (E.) sachalinensis Matsumura and E. (S.) shengmi, it is intermittently sinuous. The use of micropyle structure, size of eggs, along with chorion sculpturing, resulted useful in egg and species identification.